The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11738-012-1206-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the root nodules of Phaseolus vulgaris is induced under conditions of phosphorus deficiency

Abstract: One of the most adverse effects of phosphorus (P) deficiency on N-2-fixing legumes is the generation of harmful active oxygen species which cause oxidative stress. And although oxidative stress has been widely studied in roots and shoots of various plant species, it has not yet sufficiently been documented in bean nodules so far. In this study, two recombinant inbred lines RIL115 (P-deficiency tolerant) and RIL147 (P-deficiency sensitive) of common bean and Concesa (local variety) were inoculated separately wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Nodules have the potential to generate high levels of ROS due to high rates of bacteroid respiration, the oxidation of several proteins (nitrogenase, ferredoxin and hydrogenase) with strong reducing potentials, and autoxidation of the oxygenated form of leghemoglobin (Becana et al ., ). Oxidative stress is known to be a critical factor associated with Pi deficiency, and is caused by the overproduction of harmful ROS in the nodules of N 2 ‐fixing legumes when nodule metabolism is disturbed by either a biotic or abiotic stressor (Bargaz et al ., ). In a previous study, it was suggested that Pi deficiency‐induced oxidative stress may be implicated in down‐regulating the SNF capacity in Mm SWRI9‐inoculated plants (Nasr Esfahani et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Nodules have the potential to generate high levels of ROS due to high rates of bacteroid respiration, the oxidation of several proteins (nitrogenase, ferredoxin and hydrogenase) with strong reducing potentials, and autoxidation of the oxygenated form of leghemoglobin (Becana et al ., ). Oxidative stress is known to be a critical factor associated with Pi deficiency, and is caused by the overproduction of harmful ROS in the nodules of N 2 ‐fixing legumes when nodule metabolism is disturbed by either a biotic or abiotic stressor (Bargaz et al ., ). In a previous study, it was suggested that Pi deficiency‐induced oxidative stress may be implicated in down‐regulating the SNF capacity in Mm SWRI9‐inoculated plants (Nasr Esfahani et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Seven days after, the seedlings were inoculated with 10 mL of each strain of rhizobia Containing approximately 10 8 CFU/mL (CFU = Colony-forming unit). Plants were watered three times a week with the distillated water and the nitrogen free nutrient solution during the trial period (Bargaz et al 2013). After one week, plants randomly selected were subjected to maximal irrigation (100%), optimal irrigation (FC 1 : 80% of field capacity) and under water deficit (FC 2 : 40% of field capacity).…”
Section: Bacterial Materialmentioning
confidence: 99%
“…5 The latter, with carbon supply regulation and N feedback, contribute to regulating SNF. 43 Moreover, oxidative stress is not induced only under P-deficiency, 34,44 but also in response to high P concentration in nodules where respiration is expected to be not associated to SNF. [5][6][7][8][9][10][11][12][13][14][15][16] This is evidenced by the absence of correlation between the efficiency in use of rhizobial symbiosis and SNF.…”
Section: Relation With Oxidative Stress In N 2 -Fixing Nodulesmentioning
confidence: 99%